Genetic gains in physic nut using selection indexes - Bhering, Leonardo Lopes; Salgado, Caio Césio; Sanchez, Carlos Felipe Barrera; Laviola, Bruno Galvêas; Rosado, Tatiana Barbosa; Alves, Alexandre Alonso (Pesquisa Agropecuária Brasileira, 2012)
The objective of this work was to estimate genetic gains in physic nut (Jatropha curcas) using selection indexes and to establish the best selection strategy for the species. Direct and indirect selection was carried out using different selection indexes, totalizing 14 strategies. One hundred and seventy five families from the active germplasm bank of Embrapa Agroenergy, Brasília, Brazil, were analyzed in a randomized complete block design with two replicates. The evaluated traits were: grain yield; seeds per fruit; endosperm/seed ratio; seed weight, length, width, and thickness; branches per plant at 0.5, 1.0, and 1.5 m; plant height; stem diameter; canopy projection on rows and between lines; canopy volume; juvenility (days to the first flowering); and height of the first inflorescence. Evaluations were done during the second year of cultivation. The use of selection indexes is relevant to maximize the genetic gains in physic nut, favoring a better distribution of desirable traits. The multiplicative and restrictive indexes are considered the most promising for selection.

O objetivo deste trabalho foi estimar o ganho genético em pinhão-manso (Jatropha curcas) com uso de diferentes índices de seleção e estabelecer a melhor estratégia de seleção para a espécie. A seleção direta e indireta foi realizada com diferentes índices de seleção, o que totalizou 14 estratégias. Foram analisadas 175 famílias pertencentes ao banco ativo de germoplasma da Embrapa Agroenergia, em blocos ao acaso, com duas repetições. Foram avaliadas as variáveis: produtividade de grãos; sementes por fruto; razão endosperma/semente; peso, comprimento, largura e espessura de sementes; número de ramos a 0,5, 1,0 e 1,5 m; altura de plantas; diâmetro do caule; projeção da copa nas linhas e nas entrelinhas; volume da copa; juvenilidade (dias até o florescimento); e altura de inserção da primeira inflorescência. As avaliações foram realizadas durante o segundo ano de cultivo. A utilização de índices de seleção é relevante para maximizar os ganhos genéticos em pinhão-manso e favorece uma melhor distribuição de características desejáveis. Os índices multiplicativos e restritivos são considerados os mais promissores para uso na seleção.
Keywords: Jatropha curcas; Biodiesel; Canopy volume; Cerrado; Juvenility; Seed size